Bionic Prototyping of Honeycomb Patterned Polymer Composite and Its Engineering Application. Issue 17 (22nd November 2018) - Korde, Jay M.; Shaikh, Mohsin; Kandasubramanian, Balasubramanian
ABSTRACT: Polymeric honeycombs have always enticed researchers due to their lightweight, high stiffness-to-weight ratio, and well developed energy absorption characteristics, owing which they find themselves extensively used in automotive and aerospace engineering. Simultaneously, additive manufacturing methodologies offers enticing pathway for prototyping of functional materials starring complex heterogeneous structural designs with varying wall thickness inspired from biological systems, paving way for augmenting the mechanical and physical properties for specifically tailored applications. We have portrayed potential and possible challenges for 3D printing for prototyping of polymeric honeycomb composites, not constrained by existing engineering principles, offering designer proficiency to build resilient architectures. GRAPHICAL ABSTRACT: